A multi-sector version of the post-keynesian growth model - Ricardo Silva Azevedo Araujo (Universidade de São Paulo, 2015)
With this inquiry we seek to develop a disaggregated version of the post-Keynesian approach to economic growth, by showing that indeed it can be treated as a particular case of the Pasinettian model of structural change and economic expansion.  By relying upon vertical integration it becomes possible to carry out the analysis initiated by Kaldor (1956) and Robinson (1956, 1962), and followed by Dutt (1984), Rowthorn (1982) and later Bhaduri and Marglin (1990) in a multi-sectoral model in which demand and productivity increase at different paces in each sector. By adopting this approach it is possible to show that the structural economic dynamics is conditioned not only to patterns of evolving demand and diffusion of technological progress but also to the distributive features of the economy, which can give rise to different regimes of economic growth. Besides, we find it possible to determine the natural rate of profit that makes the mark-up rate to be constant over time.